Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s10029-012-1011-5
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic preference and outcomes for elective inguinal hernia repair: a comparative analysis of public and private hospitals

Abstract: Patients undergoing surgery in the private sector are younger, healthier, prefer general anaesthesia and have higher day case rates compared to public sector. The short- and long-term outcomes are similar between public and private sectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Sanjay et al [ 44 ] studied patient selection criteria, anesthetic preferences and outcomes of elective inguinal hernia repair in public and private sectors in England. The authors found that the mean wait time for patients undergoing hernia repair is 129 days in the public sector (range 16–379 days) and 15 days (range 8–61 days; p = 0.001) in the private sector.…”
Section: Resultsmentioning
confidence: 99%
“…Sanjay et al [ 44 ] studied patient selection criteria, anesthetic preferences and outcomes of elective inguinal hernia repair in public and private sectors in England. The authors found that the mean wait time for patients undergoing hernia repair is 129 days in the public sector (range 16–379 days) and 15 days (range 8–61 days; p = 0.001) in the private sector.…”
Section: Resultsmentioning
confidence: 99%
“… 32 Furthermore, Sanjay et al found no significant differences in postoperative complications following inguinal hernia repair in private versus public hospitals. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Although LA is being more frequently used as a technique of choice, 1 GA is still the most applied anesthetic technique in most hospitals. 4,37 Because of the fact that every anesthetic technique has its benefits as well as its drawbacks, it is necessary for clinicians to make a proper decision in order to perform the best possible treatment.…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%
“…D espite the fact that open inguinal hernia repair is one of the most common surgical procedures performed with local anesthesia (LA), regional anesthesia (RA), and general anesthesia (GA) worldwide, there is still no general agreement regarding the best anesthetic technique with which it can be performed. Although LA is currently preferred to other types of anesthesia in specialized centers, 1 this practice is not reflected in community hospitals, where most of these procedures are performed. 2 Regarding some risks (referring to those with cardiorespiratory comorbidity), the deployment of up-to-date, short-acting anesthetic drugs enabled GA to be quite suitable for use in day surgery.…”
mentioning
confidence: 99%